Pengaruh Lingkungan Kerja Terhadap Semangat Kerja Pegawai Pada Kantor Kecamatan Kapuas Kuala - Rico Rico; Misyatul Adawiyah; Ushansyah Ushansyah; Nafiah Ibnor (Journal on Education, 2023)
In any institution or organization, the human factor plays a bigger role in producing a more advanced orientation. In addition to the need for high morale, the Kapuas Kuala District Office also requires a conducive work environment for its employees to be able to channel their performance towards office success. If employees do not do a proper job, the expected results will not be fulfilled and the results will not be as expected. In order to achieve the goals of the Kapuas Kuala District Office more effectively, employees who have high morale are needed. In addition, a positive work environment is needed to increase employee morale and improve performance. A pleasant and supportive work environment can increase the enthusiasm of Kapuas Kuala Regency office employees because a complete environment and facilities will encourage employees to do their jobs well, feel happy, and avoid laziness so as to increase motivation in carrying out their duties. In this research the method used is a qualitative method with research that is descriptive in nature and also uses analysis. Researchers also used a phenomenological approach to help determine the influence of the work environment on employee morale at the Kapuas Kuala District Office.